A novel method to rapidly evaluate the quality of the traditional Chinese medicine Gentiana straminea Maxim. using near infrared spectroscopy coupled with chemometrics. Issue 7 (8th August 2020) - Li, Peipei; Luan, Zhenjie; Li, Duo; Meng, Xiaoping; Sun, Jing
Abstract: The test is to control quality of Gentiana straminea Maxim. by near infrared spectroscopy. Samples were collected throughout Qinghai-Tibet Plateau, in which the bioactive ingredients were gentiopicroside and loganic acid. Sample set was divided using concentration gradient method. Modeling optimization was processed with a designed orthogonal test L9 (3 3 ). Pretreatment of spectra was multiplicative scatter correction + second derivative, and partial least square was used to establish model. The model showed high R and low root mean square error. Moreover, residual predictive deviation was 3.14. The present quantitative model can fast and accurately determine the quality of G. straminea .